Perkembangan Motif Batik di Wonosobo - Alamsyah Alamsyah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2019)
Wonosobo Batik historically could be traced in Hindu period with the discovery of Syiva wore Parang motif. At the end of the 19th century Wonosobo batik motif was seen in clothes worn by traditional Dutch East Indies officers. In the post-independence period Wonosobo batik was also seen to be worn by the community. Motif used was dominated by Parang motif (machete) Lereng motif (slope) with dark and darkish color. The existence of batik was reappeared at the beginning of 21st century dominated by Carica and purwaceng motifs. These motifs were considered to have local peculiarities of Wonosobo. From these motifs carica combination motif had developed. The motifs which were combined with carica such as Sulur, Sekar Jagat, Kawung, Wayang, Lereng, Lubang Sewu, Kopi, Cabe, Teh, Rejeng, Sidomukti, Topeng, and etc. It meant that Wonosobo batik motifs were varies by adopting potential and local culture